2015
DOI: 10.1002/phar.1623
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pathophysiology, and Management of Androgen Deficiency in Men with Metabolic Syndrome, Type 2 Diabetes Mellitus, or Both

Abstract: The prevalence of type 2 diabetes mellitus (T2DM) and metabolic syndrome (MetS) has increased in the United States over the past 40 years. These conditions, long linked with many cardiovascular complications, have recently been linked with androgen or testosterone deficiency in men. Several pathophysiologic hypotheses exist regarding this association, with the most widely reported a relationship to obesity and insulin resistance. Several randomized trials have confirmed that when testosterone replacement thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…In concordance, TRT in nine men with T1DM, erectile dysfunction, and hypogonadism improved in glycemic control, lipid profiles, and erectile function (104). Note that some observational studies have reported that TRT increases cardiovascular events in patients with metabolic syndrome (119). However, the Food and Drug Administration in the US has reviewed these reports and found them to be seriously flawed (22).…”
Section: Childhoodmentioning
confidence: 78%
See 1 more Smart Citation
“…In concordance, TRT in nine men with T1DM, erectile dysfunction, and hypogonadism improved in glycemic control, lipid profiles, and erectile function (104). Note that some observational studies have reported that TRT increases cardiovascular events in patients with metabolic syndrome (119). However, the Food and Drug Administration in the US has reviewed these reports and found them to be seriously flawed (22).…”
Section: Childhoodmentioning
confidence: 78%
“…Testosterone replacement therapy (TRT) in men with T2DM improved some of the key parameters associated with metabolic syndrome in several observational, retrospective, and prospective trials (38,55,79,119). In particular, body weight, waist circumference, blood pressure, heart rate, fasting blood glucose and insulin sensitivity, as well as HbA 1c , triglycerides, cholesterol, and low-density lipoprotein levels were significantly improved in type 2 diabetic men receiving TRT for at least 24 mo (34,123,141).…”
Section: Childhoodmentioning
confidence: 99%
“…Conflicting evidence suggests that testosterone therapy in hypogonadal men with type 2 diabetes may increase quality of life or improve sexual function (44,(94)(95)(96)(97)(98). Studies assessing whether testosterone treatment in hypogonadal men with diabetes can reduce glycated hemoglobin (A1C) values have also produced mixed results (93,94,(99)(100)(101)(102)(103)(104). A nonrandomized, ongoing, observational study of testosterone-treated men with hypogonadism with (40%) or without diabetes showed reductions in weight, visceral obesity, abdominal circumference, as well as decreased hypertension and insulin resistance over a 5-year study interval (105,106).…”
Section: Hypogonadismmentioning
confidence: 99%
“…Due to improved public health conditions worldwide, the average life expectancy of humans is longer than ever before. In addition, more aging men suffer from androgen deficiency (AD) or hypogonadism, which are becoming increasingly important public health issues (Araujo et al ., ; Taylor et al ., ). Hypogonadism can present as many symptoms, including low libido, erectile dysfunction, osteoporosis, muscle weakness, and metabolic disorders.…”
Section: Introductionmentioning
confidence: 97%